Identifikasi Genetik Menggunakan Marker Mikrosatelit dan Hubungannya dengan Sifat Kuantitatif pada Sapi - . Maskur; . Muladno; B Tappa (Media Peternakan, 2007)
The occurrence of genetic changes in Bali and Brangus cattle crossing and it's relationship to quantitative traits (e.g. growth and birth weight) were identified using microsatellite markers. Sixteen microsatellite loci were amplified using polymerase chain reaction (PCR) technique, the amplified products were then separated on vertical discontinuous polyacrylamide gel electrophoresis (PAGE) and silver-staining method was applied to detect the fragment. The evaluation to the stability and allele inheritance pattern were checked using Chi-Square segregation analysis. The results of this research showed that allele numbers average detected in Brangus and Bali cattle and their progeny were 2.31, 2.56, and 2.75 respectively. At most microsatellite loci, the allele distributions incline to concentrate and to form bimodal trend. Of 16 micro satellite loci tested, 5 microsatelitte markers namely INRA 037, HEL 9, CSSM 66, INRA 035 and ETH 225 indicated a significant response to average daily gain. In terms of birth weight, a significant response was shown by INRA 037. Key word: microsatellite, PCR, genotype, inheritance, allele